PENGARUH PENERAPAN TEKNIK TWO STAY TWO STRAY DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 15 PADANG TAHUN PELAJARAN 2013-2014 - Rahmawati, Welly; Rismen, Sefna; Husna, Husna (Pendidikan Matematika, 2014)
ABSTRAKÂ This research was grounded by the studentsâ low understanding in mathematics concept and their less chance to share information and ideas with peers. This research was aimed at reveal whether the use of Two Stay Two Stray technique could improve the studentsâ understanding in mathematics concept better than that of the conventional one. This was an experimental research. The population of the research was the students in class VIII of SMPN 15 Padang. As class VIII.1 was an excellent class, it was excluded. The sample was taken by using random sampling technique. Choosen as class of sampel is VIII.3 as experiment class and of VIII.5 as control class. The data of the research was gotten from post-test. It was an essay test that consisted of 5 items whose reliability was 0,92. The result of hypothesis test showed that the value of thitung (2,8693) was bigger than ttabel (1,67) in which Î±=0,05. This result indicated that the use of Two Stay Two Stray technique could improve the studentsâ understanding in mathematics concept better than that of the conventional one in class VIII of SMPN 15 Padang.